MODELING OF SYSTEM FOR MONITORING OF RISKS IN THE TRANSPORT (Transport systems and technologies, 2021)
The article deals with the actual problems of modeling the processes for monitoring risks in transport. This monitoring involves determining the state of transport objects, as well as procedures for minimizing the consequences of situations caused by the onset of risks. The article discusses the problems of effective creation of system for monitoring of risks in transport based on the use of appropriate models. The article proposes modeling this system based on situational-semantic model. The approach proposed would contribute to recognition of risks and generation of management decisions to eliminate their consequences. The proposed situational-semantic model allows: to predict the behavior of complex transport objects and transport infrastructure objects; take into account the possibility of emergence of new transport objects and processes for ensuring their functioning in conditions of minimizing possible risks; respond adequately to local and global factors of influence on transport objects; dynamically change the structure of the system; take into account new data to predict the development and improvement of relevant transport objects; predict the development of processes to ensure minimization of risks and the consequences of them.
Keywords: model, modeling, information system, transport risks, monitoring of processes, semantic measures, situational-semantic measures.